Chemo-immunotherapy for metastatic non-squamous NSCLC in a patient with HIV infection: A case report - Inno, Alessandro; Lattuada, Emanuela; Foti, Giovanni; Gori, Stefania (Frontiers in Oncology, 2023)
Activity and safety data of chemo-immunotherapy for patients with metastatic NSCLC and known HIV infection are still limited, since HIV-positive patients were generally excluded from clinical trials. Here we report the case of a metastatic NSCLC patient with HIV infection and undetectable viral load treated with first-line chemo-immunotherapy (pembrolizumab, carboplatin and pemetrexed), achieving a meaningful and durable objective response, with no treatment-related adverse events and no HIV-related complications. This report suggests that NSCLC patients with virologically controlled HIV infection can be safely treated with chemo-immunotherapy and should not be excluded from this treatment based on their viral infection only.